The relationship of father's knowledge and support as a breastfeeding father on exclusive breastfeeding in the working area of Public Health Center Batanghari Hospital East Lampung - Meilia Rahmawati Kusumaningsih; Muliatul Jannah; Vera Yulvina (Alma Ata University Press, 2024)
Background: Exclusive breastfeeding coverage in Lampung Province in 2020 was 70.1%, yet it still did not meet the expected target. Many factors influenced the success of exclusive breastfeeding. In providing breast milk, the father played a major role for the success. Father's knowledge and support in breastfeeding issues were the first thing the fathers needed to have to support breastfeeding practices. The fathers' support for the breastfeeding process was still lacking as society believed that breastfeeding was only the mother's duty. The support that a father could provide as a Breastfeeding Father could be in the form of helping with child care, helping with household chores, and providing food or other needs related to the breastfeeding process. Preliminary studies showed a lack of support from fathers for breastfeeding mothers at the Batanghari Lampung Community Health Center Objective: The purpose of this study was to determine the relationship between the knowledge and the father's support as a breastfeeding father towards exclusive breastfeeding. Method: This research was conducted in the Work Area of the Batanghari Inpatient Health Center, East Lampung in January - February 2023. The sample used was the fathers of infants aged 6-12 months in the Work Area of the Batanghari Inpatient Health Center, East Lampung, as many as 63 respondents obtained using accidental sampling technique . This research was a quantitative study using the Cross Sectional Study approach, analyzed by using the chi square test (α=0.05) for bivariate analysis. Results: The results of this study indicates that there was a real relationship between the father's knowledge as a breastfeeding father and the father's support as a breastfeeding father on exclusive breastfeeding in the Work Area of the Batanghari Inpatient Health Center, East Lampung with p-values of 0.038 and 0.010. Conclusions: There is a significant relationship between father's knowledge and the father's support as a breastfeeding father and exclusive breastfeeding in the Batanghari Inpatient Health Center, East Lampung working area.